Approaches to the syllable - Mott, Brian Leonard (Linguistica (Ljubljana), 2017)
In this paper, which looks back at some of the principal ways of viewing the syllable that have been proposed and attempts to assess their relative validity, I will firstly refer to evidence for the existence of the syllable and lend support to the argument that the syllable must be part of speakers' phonological knowledge because, not only can they count syllables, but they also know what sound sequences are permissible in them in their native language. Moreover, in this same vein I will also recall the fact that the syllable is the domain of many phonological processes (in English, note aspiration and the glottalling, tapping and rhotacization of t, for example). Finally, I will defend the analysis of English syllabification proposed by Wells in the Longman Pronunciation Dictionary over and against other traditional linear models and the more abstract nonlinear models, while recognizing that Wells% hypothesis still leaves unresolved some issues involving the presence/absence of phonetic correlates of morpheme boundaries.
Keywords: angleščina; English; fonologija; zlog